2003
DOI: 10.1554/0014-3820(2003)057[0261:gibtsh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Isolation Between Two Sympatric Host-Plant Races of the European Corn Borer, Ostrinia Nubilalis Hübner. I. Sex Pheromone, Moth Emergence Timing, and Parasitism

Abstract: Adaptation to different environments may be a powerful source of genetic differentiation between populations. The biological traits selected in each environment can pleiotropically induce assortative mating between individuals of these genetically differentiated populations. This situation may facilitate sympatric speciation. Successful host shifts in phytophagous insects provide some of the best evidence for the ecological speciation that occurs, or has occurred, in sympatry. The European corn borer, Ostrinia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
154
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(164 citation statements)
references
References 70 publications
9
154
0
1
Order By: Relevance
“…Accordingly, ECB larvae were found to perform better than O. scapulalis larvae on maize, and conversely to perform less well on mugwort, indicative of physiological specialization (Calcagno et al 2007). In addition, the two Ostrinia sibling species differ with respect to development time (Thomas et al (2003), but see Malausa et al 2005). Natural enemies could also have promoted the divergence, since both the identity of parasitoids and their prevalence differ between maize and mugwort (Thomas et al 2003;Pélissié et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, ECB larvae were found to perform better than O. scapulalis larvae on maize, and conversely to perform less well on mugwort, indicative of physiological specialization (Calcagno et al 2007). In addition, the two Ostrinia sibling species differ with respect to development time (Thomas et al (2003), but see Malausa et al 2005). Natural enemies could also have promoted the divergence, since both the identity of parasitoids and their prevalence differ between maize and mugwort (Thomas et al 2003;Pélissié et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On Cuba, where anole diversity is highest, more than 60 species occur over an area of only 110 000 km 2 (Rodríguez-Schettino 1999). Most anole species on Cuba and other Greater Antillean islands result from within-island processes (Losos & Schluter 2000), leading some authors to suggest that sympatric speciation plays a part in anole diversification (Shaw et al 2000; Thomas et al 2003). However, several lines of evidence suggest that geographical processes play the dominant role in intraisland anole speciation.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic, ecological and biological studies in western Europe (Bourguet et al, 2000;Martel et al, 2003;Thomas et al, 2003;Malausa et al, 2007a;Malausa et al, 2007b) have shown that the ECB and ABB are sibling species (Frolov et al, 2007). Each is adapted to its own principal host plants (maize for the ECB and hop, mugwort and hemp for the ABB), as shown by host choice for oviposition and larval feeding performance in reciprocal infestation experiments Calcagno et al, 2007;Malausa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The pheromone communication system is a key trait involved in reproductive isolation within the genus Ostrinia (Cardé et al, 1975;Huang et al, 1997;Huang et al, 2002;Thomas et al, 2003;Bontemps et al, 2004;Takanashi et al, 2005). Natural populations of both the ECB and ABB have a polymorphic communication system with two different blends of the female sex pheromone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation